2017
DOI: 10.1038/ng.3900
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent SPI1 (PU.1) fusions in high-risk pediatric T cell acute lymphoblastic leukemia

Abstract: The outcome of treatment-refractory and/or relapsed pediatric T cell acute lymphoblastic leukemia (T-ALL) is extremely poor, and the genetic basis for this is not well understood. Here we report comprehensive profiling of 121 cases of pediatric T-ALL using transcriptome and/or targeted capture sequencing, through which we identified new recurrent gene fusions involving SPI1 (STMN1-SPI1 and TCF7-SPI1). Cases positive for fusions involving SPI1 (encoding PU.1), accounting for 3.9% (7/181) of the examined pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
141
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(149 citation statements)
references
References 63 publications
7
141
1
Order By: Relevance
“…The integrated analysis of gene alterations in two recent series of pediatric T-ALL provided an enlarged view of the genomic landscape in this heterogenous disease (20,23). However, complex interplay of gene fusions, sequence abnormalities, and transcriptional expression profiles, especially in adult cases, needs to be further addressed to refine the current model of T-ALL leukemogenesis and to reveal potential new biomarkers and therapeutic targets.…”
mentioning
confidence: 99%
“…The integrated analysis of gene alterations in two recent series of pediatric T-ALL provided an enlarged view of the genomic landscape in this heterogenous disease (20,23). However, complex interplay of gene fusions, sequence abnormalities, and transcriptional expression profiles, especially in adult cases, needs to be further addressed to refine the current model of T-ALL leukemogenesis and to reveal potential new biomarkers and therapeutic targets.…”
mentioning
confidence: 99%
“…2,9,10,[14][15][16] Detailed analysis of our next-generation sequencing data 9,10,18 revealed that 14 of 41 JAK3-mutant T-ALLs have either a homozygous JAK3 mutation or 2 different JAK3 mutations ( Figure 1A). In a recently published exome sequencing study, 3 of 20 JAK3-mutant T-ALL patient cases were reported to harbor 2 JAK3 mutations.…”
Section: Resultsmentioning
confidence: 99%
“…11,12 Between 10% and 16% of patients with T-ALL carry at least 1 mutation in JAK3. 2,9,10,[14][15][16] A more detailed analysis presented here shows that up to a third of these patient cases harbor a second JAK3 mutation, and we investigated the biological significance of having multiple JAK3 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Centriolar assembly protein–T‐cell acute lymphocytic leukemia 1 (STIL‐TAL1), caused by the deletion of 1p32, and mixed lineage leukemia–super elongation complex subunit (MLL‐MLLT1), caused by t(11;19), are observed recurrently in T‐ALL, although these fusions are not used for treatment stratification. Recently, recurrent gene fusions involving Spi‐1 proto‐oncogene ( SPI1 ) were identified in 3.9% of 121 pediatric T‐ALL cases investigated, which was associated with poor overall survival …”
Section: Recent Advances In Molecular Biology Of Pediatric Allmentioning
confidence: 99%